2009
DOI: 10.1111/j.1755-0998.2009.02595.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers for the roman, Chrysoblephus laticeps (Teleostei: Sparidae), an overexploited seabream from South Africa

Abstract: Eleven polymorphic microsatellite loci were developed from an enrichment library of the roman, Chrysoblephus laticeps, and characterized for 40 individuals collected in Africa's largest and oldest Marine Protected Area (MPA), the Tsitsikamma National Park. The number of alleles per locus ranged from three to 19, and heterozygosities ranged from 0.20 to 0.85. A significant departure from Hardy-Weinberg equilibrium was detected for one locus, and linkage disequilibrium was identified among three pairs of loci. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Previous studies in patients with heart failure [18], chronic PH [19], arrhythmogenic right ventricular disease [20] and in patients referred for cardiac surgery [21] have found that strain imaging is more precise in the quantification of RV function than the global parameters RVFAC and TAPSE. The complex shape of the right ventricle and the monoplane measurement are one reason why RVFAC has to be used with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with heart failure [18], chronic PH [19], arrhythmogenic right ventricular disease [20] and in patients referred for cardiac surgery [21] have found that strain imaging is more precise in the quantification of RV function than the global parameters RVFAC and TAPSE. The complex shape of the right ventricle and the monoplane measurement are one reason why RVFAC has to be used with caution.…”
Section: Discussionmentioning
confidence: 99%
“…2009) of which 41 (36%) are commonly found around the southern African coast (Heemstra & Heemstra 2004). Although sparids are a prominent feature to the South African fishery, microsatellite markers have only been developed for one species, the roman Chrysoblephus laticeps (Teske et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphic markers isolated were tested with four previously isolated microsatellites from other studies, (Piñera et al. 2006; Teske et al. 2009), across nine additional species.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen microsatellite markers were used in this study; LLt002,LLt005,LLt006,LLt007,LLt011,LLt014,LLt020,LLt024 and LLtr004 were isolated in white steenbras (from Reid et al 2012), while PBt003, PBt007, PBt013, PBt018, PB106 (from Reid et al 2012 and Clat11 (from Teske et al 2009) were isolated from related species. These loci were designed into multiplexes and amplified using the Quantitect ® Multiplex PCR Kit (QIAGEN ® ).…”
Section: Mitochondrial Control Region Sequencing and Microsatellite Gmentioning
confidence: 99%